Measuring the Schmidt number of parametric down conversion by exploiting photon distribution - Cohen, Lior; Matekole, Elisha S.; Pilnyak, Yehuda; Istrati, Daniel; Dowling, Jonathan P.; Eisenberg, Hagai S. (AVS Quantum Sci., 2023)
The Schmidt number quantifies the number of modes and is mainly used as a measure for the quality of entanglement. We theoretically compute the photon distribution of type-I spontaneous parametric down conversion (SPDC) with an arbitrary Schmidt number. The photon distribution is used for a novel method to measure the Schmidt number. This method requires only two on–off single-photon detectors with no photon number or temporal resolution. The method works in the strong pumping regime where high photon numbers are non-negligible. We experimentally demonstrate the method for type-II SPDC. The easy and fast measurement of the Schmidt number has a broad range of applications from the calibration of strong pump SPDC and entanglement sources to multi-photon quantum interference and Gaussian boson sampling.